A King's Apotheosis: Iconography, Text, and Politics from a Classic Maya Temple at Holmul. Issue 2 (June 2016) - Estrada-Belli, Francisco; Tokovinine, Alexandre
Abstract : Excavations at the ancient Maya city of Holmul, Petén, have led to the discovery of a building decorated with an intricately carved and painted plaster frieze. The iconography of the frieze portrays seated lords, mountain spirits, feathered serpents, and gods of the underworld engaged in the apparent rebirth of rulers as sun gods. Large emblems carved on the side of the building identify the structure as a shrine for ancestor veneration. A dedicatory text carved along the bottom of the frieze contains a king list and references to the political and familial ties of the ruler who commissioned the temple. Together, the iconography and text of this structure provide evidence of function and meaning. They also shed new light on a century during Classic Maya history known as the Tikal "Hiatus, " for which a limited number of texts are available. The information derived from this monument also broadens our understanding of the nature of hegemonic relationships among Classic Maya states.